2020
DOI: 10.3389/fcell.2020.00696
|View full text |Cite
|
Sign up to set email alerts
|

Relevance Function of Linc-ROR in the Pathogenesis of Cancer

Abstract: Long non-coding RNAs (lncRNAs) are the key components of non-coding RNAs (ncRNAs) with a length of 200 nucleotides. They are transcribed from the so-called "dark matter" of the genome. Increasing evidence have shown that lncRNAs play an important role in the pathophysiology of human diseases, particularly in the development and progression of tumors. Linc-ROR, as a new intergenic non-protein coding RNA, has been considered to be a pivotal regulatory factor that affects the occurrence and development of human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 145 publications
(224 reference statements)
0
35
0
Order By: Relevance
“…LincRNAs have been identified as critical regulators in various cellular processes, including cancer initiation and progression. 30 31 Although it has been found that LINC01140 is overexpressed in gastric cancer 17 and regulates the inflammatory response during pulmonary fibrosis, 18 the role of LINC01140 in other disease, including LC, is still not completely understood. Recently, an outstanding work by Allou et al revealed that mutations involving lncRNA loci can result in human Mendelian disease.…”
Section: Discussionmentioning
confidence: 99%
“…LincRNAs have been identified as critical regulators in various cellular processes, including cancer initiation and progression. 30 31 Although it has been found that LINC01140 is overexpressed in gastric cancer 17 and regulates the inflammatory response during pulmonary fibrosis, 18 the role of LINC01140 in other disease, including LC, is still not completely understood. Recently, an outstanding work by Allou et al revealed that mutations involving lncRNA loci can result in human Mendelian disease.…”
Section: Discussionmentioning
confidence: 99%
“…ROR was initially discovered as a promoter of the reprogramming process, and it was shown to contribute to the maintenance of pluripotent and embryonic stem cells via inhibition of cellular stress signaling pathways ( 159 ). Elevated ROR expression has been detected across cancer cell lines ( 160 ). Recent studies have shown that ROR promotes EMT in various cancers ( 161 , 162 ).…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%
“…Aberrations in the ceRNA network can lead to pathological conditions and cancer development [229]. LINC-ROR, acting as a ceRNA in ESCs, is involved in the occurrence and development of different human tumors (breast cancer, colorectal cancer, pancreatic cancer, hepatocellular carcinoma), and it represents a potential biomarker with clinical significance that can be used as therapeutic target [230]. In colon cancer stem cells, as in ESCs, LINC-ROR acts as a ceRNA to prevent miR-145-mediated suppression of NANOG, OCT4, and SOX2 TFs to regulate cell proliferation and chemosensitivity [231].…”
Section: Regulation Of Mirnas Through Competitive Endogenous Rnas In Escs and Cscsmentioning
confidence: 99%